Development of vision based automated guided vehicle - Ahmad Amjad, Ahmad Daud (2022)
Automated guided vehicles (AGV) are important part of the logistic transport system especially in big industry. They are used commonly for ease the worker or employer especially in heavy task in factory such as automotive industry. The basic requirement for a mobile robot to move autonomously is that it understands its current position in relation to its surroundings, which is referred to as mobile robot localization. In real world applications, however, interferences and diverse environmental disturbances hinder mobile robot localization. The goal of this project is to mapping and scanning the location of a mobile robot in a known, static, and indoor environment. The lidar sensor, Jetson Nano and the ultrasonic sensor are used in this project to manage the target to mapping and scanning the environment especially indoor. By using Jetson Nano as a 'brain' of this project it can control the prototype or model to functioning other sensor to manage the mapping and scanning while the prototype move surrounding. Lidar sensor referred to as "laser scanning" or "2D scanning." The method creates a 3D depiction of the studied area using eye-safe laser beams. The studies were done out utilising a two wheeled mobile robot to collect data about the environment by mapping and scanning update time by time to get the full scanning in some space. The ultrasonic and lidar sensor was effectively used to increase the estimation accuracy of the mobile robot localisation utilising the created drive system and measurement models.